Role of school council in the performance of primary level students - Zahida Habib (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2014)
In this era of globalization school council plays a vital role towards the performance of students in primary education. Comparative research may help to assess the pace of project development, and explore the impediments for adopting timely remedial measures. This research aims to explore the role of school council in Community Model Schools and Govt Girls Primary Schools. The target population of the study comprises of all Community Model Schools and Govt Girls Primary Schools in Punjab, Pakistan. However, the accessible population was three fifty schools (175 Community Model Schools and 175 Govt Girls Primary Schools) from thirty five districts of the Punjab. To see the role of school council and academic performance of students, a sample from each district is selected based on ten head mistresses, twenty teachers, ten administrators, one hundred students and one hundred parents are randomly selected. Documentary facts were used for seeing the role of school council and academic performance of students in both types of schools, as well as a questionnaire of five point Likert scale was designed to investigate and collect data about the students' performance and role of school council. Data is analyzed by using descriptive statistics as well as t-test to compare both types of schools at 5% level of significance. Results indicate that Community Model Schools are better in students' performance due to the role of school council than Govt. Girls Primary Schools.
Keywords: 330; school council; students' performance; primary education; community model; schools; girls' primary schools